Tuberculosis Immunity: Opportunities from Studies with Cattle - W. Ray Waters; Mitchell V. Palmer; Tyler C. Thacker; William C. Davis; Srinand Sreevatsan; Paul Coussens; Kieran G. Meade; Jayne C. Hope; D. Mark Estes (Clinical and Developmental Immunology)
Mycobacterium tuberculosis and M. bovis share >99% genetic identity and induce similar host responses and disease profiles upon infection. There is a rich history of codiscovery in the development of control measures applicable to both human and bovine tuberculosis (TB) including skin-testing procedures, M. bovis BCG vaccination, and interferon-γ release assays. The calf TB infection model offers several opportunities to further our understanding of TB immunopathogenesis. Recent observations include correlation of central memory immune responses with TB vaccine efficacy, association of SIRPα+ cells in ESAT-6:CFP10-elicited multinucleate giant cell formation, early γδ T cell responses to TB, antimycobacterial activity of memory CD4+ T cells via granulysin production, association of specific antibody with antigen burden, and suppression of innate immune gene expression in infected animals. Partnerships teaming researchers with veterinary and medical perspectives will continue to provide mutual benefit to TB research in man and animals.